Respuesta :
4x + 15 = 6x + -11
Reorder the terms:
15 + 4x = 6x + -11
Reorder the terms:
15 + 4x = -11 + 6x
Solving
15 + 4x = -11 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
15 + 4x + -6x = -11 + 6x + -6x
Combine like terms: 4x + -6x = -2x
15 + -2x = -11 + 6x + -6x
Combine like terms: 6x + -6x = 0
15 + -2x = -11 + 0
15 + -2x = -11
Add '-15' to each side of the equation.
15 + -15 + -2x = -11 + -15
Combine like terms: 15 + -15 = 0
0 + -2x = -11 + -15
-2x = -11 + -15
Combine like terms: -11 + -15 = -26
-2x = -26
Divide each side by '-2'.
x = 13
Simplifying
x = 13
Reorder the terms:
15 + 4x = 6x + -11
Reorder the terms:
15 + 4x = -11 + 6x
Solving
15 + 4x = -11 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
15 + 4x + -6x = -11 + 6x + -6x
Combine like terms: 4x + -6x = -2x
15 + -2x = -11 + 6x + -6x
Combine like terms: 6x + -6x = 0
15 + -2x = -11 + 0
15 + -2x = -11
Add '-15' to each side of the equation.
15 + -15 + -2x = -11 + -15
Combine like terms: 15 + -15 = 0
0 + -2x = -11 + -15
-2x = -11 + -15
Combine like terms: -11 + -15 = -26
-2x = -26
Divide each side by '-2'.
x = 13
Simplifying
x = 13
x= 13 because you have to add the x all to the left side than minus eleven from both sides which would equal -2x=-26 then divide by -2 which would equal x=13